Exploring Organizational Citizenship Behavior and its Critical Link to Employee Engagement for Effectual Human Resource Management in Organizations - Mansoor, Narmeen; Aslam, Hassan Danial; Javad, Tasawar; Ashraf, Fawad; Shabbir, Farooq (Richtmann Publishing, 2012)
Organizational Citizenship is one of the emerging management concepts that are being emphasized for its uniqueconstitution. Organizations strive to establish organizational citizenship behavior (OCB) among their employees for attainingexceptionally motivated workforce. The purpose of this paper was to explore Organizational Citizenship Behavior (OCB) and itsimportance in recent times. It elaborates the extent to which five core job characteristics of Job Characteristic Model (JCM) leadto organizational citizenship and its impact of employee engagement and commitment on OCB. Qualitative research design hasbeen adopted where extensive literature resources have been elaborated in order to understand the relationship. Researchershave presented a detailed model explaining Organizational Citizenship Behavior (OCB) and its critical link with JCM and withemployee commitment and job engagement. Findings reveal that four dimensions (task variety, task identity, task significanceand task autonomy) Job Characteristic Model (JCM), and employee engagement produces positive impact on OCB. However,the impact of employee commitment on OCB is not yet obvious.